Modeling Hospital Information Systems (Part 1): The Revised Three-layer Graph-based Meta Model 3LGM2 - Winter, A.; Brigl, B.; Wendt, T. (Methods of Information in Medicine, 2003)
Objectives: Not only architects but also information managers need models and modeling tools for their subject of work. Especially for supporting strategic information management in hospitals, the meta model 3LGM2 is presented as an ontological basis for modeling the comprehensive information system of a hospital (HIS).Methods: In a case study, requirements for modeling HIS have been deduced. Accordingly 3LGM2 has been designed to describe HIS by concepts on three layers. The domain layer consists of enterprise functions and entity types, the logical tool layer focuses on application components and the physical tool layer describes physical data processing components. In contrast to other approaches a lot of inter-layer-relationships exist. 3LGM2 is defined using the Unified Modeling Language (UML).Results: Models of HIS can be created which comprise not only technical and semantic aspects but also computer-based and paper-based information processing. A software tool supporting the creation of 3LGM2 compliant models in a graphical way has been developed. The tool supports in detecting those shortcomings at the logical or the physical tool layers which make it impossible to satisfy the information needs at the domain layer. 3LGM2 can also be used as an ontology for describing HIS in natural language.Conclusions: Strategic information management even in large hospitals should be and can be supported by dedicated methods and tools. Although there have been good experiences with 3LGM2 concerning digital document archiving at the Leipzig University Hospital, which are presented in part 2, the benefit of the proposed method and tool has to be further evaluated.
Keywords: Hospital information systems; hospital information system management; information management; models for hospital information systems; ontology; organizational issues